Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions (STAD) Pada Mata Pelajaran Dasar-Dasar Ketenagalistrikan - Ica Jelita Putri; Sukardi Sukardi (Departement of Electrical Engineering Universitas Negeri Padang, 2025)
This study aims to examine the effectiveness of the Student Teams Achievement Divisions (STAD) cooperative learning model in improving students' learning outcomes in the Basic Electrical Engineering subject at SMKN 1 Pariaman. The research was motivated by the low student achievement, with only 24% of students meeting the Learning Objective Achievement Criteria (KKTP), caused by low participation, lack of collaboration, and teaching methods that did not actively engage students. The study employed a pre-experimental method with a one-group pretest-posttest design, involving Grade X Electrical Engineering students as research subjects. Data were collected through objective tests (pretest and posttest) that had been validated and tested for reliability, then analyzed using the N-Gain Score calculation and learning mastery percentage. The results showed that the implementation of the STAD model significantly improved students' learning outcomes, with a high category of improvement in the cognitive aspect, where most students achieved mastery learning. Group interaction and team reward systems were proven effective in increasing active participation and collaborative understanding of the material. The study concludes that the STAD model is effective for teaching technical subjects in vocational schools and is recommended as an innovative alternative learning strategy to enhance student achievement.